Blood group O alleles in Native Americans: Implications in the peopling of the Americas - Estrada-Mena, Benito; Estrada Mena, Francisco Javier; Ulloa-Arvizu, Raúl; Guido, Miriam; Méndez, Rocío; Coral, Ramón; Canto, Thelma; Granados, Julio; Rodrigo Rubí-Castellanos; Rangel-Villalobos, Héctor; García-Carrancá, Alejandro (My University, 2009)
All major ABO blood alleles are found in most populations worldwide, whereas the majority of Native Americans are nearly exclusively in the O group. O allele molecular characterization could aid in elucidating the possible causes of group O predominance in Native American populations. In this work, we studied exon 6 and 7 sequence diversity in 180 O blood group individuals from four different Mesoamerican populations. Additionally, a comparative analysis of genetic diversity and population structure including South American populations was performed. Results revealed no significant differences among Mesoamerican and South American groups, but showed significant differences within population groups attributable to previously detected differences in genetic drift and founder effects throughout the American continent. Interestingly, in all American populations, the same set of haplotypes O1, O1v, and O1v(G542A) was present, suggesting the following: (1) that they constitute the main genetic pool of the founding population of the Americas and (2) that they derive from the same ancestral source, partially supporting the single founding population hypothesis. In addition, the consistent and restricted presence of the G542A mutation in Native Americans compared to worldwide populations allows it to be employed as an Ancestry informative marker (AIM). Present knowledge of the peopling of the Americas allows the prediction of the way in which the G542A mutation could have emerged in Beringia, probably during the differentiation process of Asian lineages that gave rise to the founding population of the continent. Am J Phys Anthropol, 2010. © 2009 Wiley-Liss, Inc.